Two-dimensional speckle-tracking echocardiographic assessment of left ventricular mechanical synchrony in clinically normal cats - Hsu YL (Dove Medical Press, 2016)
Yueh-Lun Hsu, Hui-Pi Huang Institute of Veterinary Clinical Science, Veterinary School, National Taiwan University, Taipei, Taiwan Abstract: Ventricular heterogeneity and synchrony are associated with hypertrophic cardiomyopathy in humans. Hypertrophic cardiomyopathy is commonly observed in cats. The aim of this study was to determine the presence and normal range of left ventricular mechanical heterogeneity and synchrony in clinically healthy cats using two-dimensional speckle-tracking echocardiography. Thirty-four clinically healthy cats were included in this prospective study. Two-dimensional echocardiography and two-dimensional speckle-tracking echocardiography were performed on all cats. Echocardiographic parameters, including circumferential, radial, and longitudinal strain and strain rate, heterogeneity, and synchrony, were measured. Segmental heterogeneity values in the circumferential, radial, and longitudinal directions were 13.1%±5.9%, 19.1%±10.3%, and 15.4%±6.8%, respectively. Transmural heterogeneity was -14.3%±4.6% in the circumferential direction. Left ventricular synchrony values in the circumferential, radial, and longitudinal directions were 11.7±4.2, 16.5±13.4, and 19.4±8.5 ms, respectively. Interventricular synchrony was -3.9±13.2 ms. Left ventricular heterogeneity and synchrony were noted in clinically healthy cats; segmental heterogeneity, which is characterized as longitudinal, progressively increased from the apical to the basal segments, while transmural heterogeneity, which is characterized as circumferential, progressively decreased from the endocardium to the epicardium. Keywords: feline, ventricular heterogeneity, synchrony